Study on the Optimization Path of After-school Physical Education Services in Junior High Schools under the Policy of Increasing the Physical Education Score of the Secondary School Examination - Jinjiang Qiao; Xue Wang (SHS Web of Conferences)
In the context of the increase in the value of physical education scores in the midterm examination, there is an undesirable phenomenon of “jumping the gun” in physical education, and the rapid expansion of extracurricular training institutions in physical education. Further optimisation of physical education after-school services in junior middle schools can solve these problems and promote the healthy development of young people, schools, and the society. Currently, there is almost no research on junior middle school physical education(PE) after-school service with the background of “raising the score of PE in the Chinese Middle School Examination”. This study attempts to develop an explanatory model of the factors influencing the effective implementation of junior middle school PE after-school services, and to analyse the deficiencies in the implementation of junior middle school PE after-school services in the context of the increase in the PE scores of the secondary school examination in five aspects, namely, the direct conditions, the social environment, the stakeholders, the management of the services, the service content, the form and the effect, and to propose optimisation paths, with the aim of optimising the junior middle school PE after-school services in a more scientific and systematic way. The results of the study are as follows Findings: After-school PE services in junior middle schools have problems such as the phenomenon of exam-oriented education, insufficient teachers, irrational time arrangement, too many students (≥100 students), high fees (average 80-100 RMB/class hour), low remuneration for teachers’ services (average 50-100 RMB/class hour), and low motivation of students. Conclusion and Optimisation Path: Improve the curriculum system of after-school PE service in junior middle schools, increase the government’s financial support for after-school PE service, introduce external forces to participate in after-school PE service, and create a positive atmosphere for after-school PE service.